On the Nazeris fauna of Guangxi, China. II. The species of Daming Shan (Coleoptera, Staphylinidae, Paederinae) - Hu, Jia-Yao; Li, Li-Zhen; Chen, Yan (Zootaxa, 2013)
Two new species of Nazeris Fauvel collected from Daming Shan, Guangxi Province, are described and illustrated: N. damingshanus Hu & Li, sp. n., N. longilobus Hu & Li, sp. n. An identification key to the Nazeris species from Guangxi is provided.